Pengembangan dan Evaluasi Aplikasi e-RT di Kelurahan Periuk Kecamatan Periuk Kota Tangerang - Seng Hansun; Muh Salehuddin; Marcel Bonar Kristanda (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Rukun Tetangga (RT) role as the smallest unit in the hierarchical structure of Regional Government is very important in guarding and preserving the norm and values of Indonesian people. However, in the management and services delivery at RT level various problems could be happened, such as the long services delivery time, lack of Government and local RT program socialization, and lack of the committee members support facility. A solution offered to solve these problems is by creating e-RT application that can support the services performance of RT officer as well as a means to distribute various Government and RT programs. The Community Service Program (PKM) was then be proposed and implemented with an eight months-time planning. This program got a positive support, both from the UMN Research and Community Service Institution (LPPM UMN) and the community that become the partner for this program, i.e., RT 06 in Periuk village, Periuk subdistrict, Tangerang City. The final result of this program is an e-RT application based on mobile web app, which can be easily accessed by all community members. In this article, the application evaluation is described by referring the WEBQUAL 4.0 instrument with 80.29% result.